1992
DOI: 10.1161/01.atv.12.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a monounsaturated rapeseed oil and a polyunsaturated sunflower oil diet on lipoprotein levels in humans.

Abstract: The effects of high oleic acid rapeseed oil compared with polyunsaturated fats on serum lipoprotein levels are largely unknown. Therefore, we fed 30 women and 29 men a baseline diet rich in saturated fat, which was followed by a diet rich in high oleic and low erucic acid rapeseed oil (total energy content of fat, 38%; saturates, 12.4%; monounsaturates, 16%; n-6 polyunsaturates, 6%; and n-3 polyunsaturates, 2%) and one rich in sunflower oil (total energy content of fat, 38%; saturates, 12.7%; monounsaturates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
63
2
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 38 publications
7
63
2
3
Order By: Relevance
“…Effects on serum lipids, lipoproteins, and apolipoproteins are in line with earlier intervention studies with rapeseed oil (McDonald et al, 1989;Wardlaw et al, 1991;Valsta et al, 1992;Nydahl et al, 1994). Even with the relatively high fat content of the test diets, we found lower total and LDL cholesterol levels, apo B concentrations, and LDL=HDL ratios and no differences in HDL cholesterol levels after the RO diet compared to the SAT diet.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Effects on serum lipids, lipoproteins, and apolipoproteins are in line with earlier intervention studies with rapeseed oil (McDonald et al, 1989;Wardlaw et al, 1991;Valsta et al, 1992;Nydahl et al, 1994). Even with the relatively high fat content of the test diets, we found lower total and LDL cholesterol levels, apo B concentrations, and LDL=HDL ratios and no differences in HDL cholesterol levels after the RO diet compared to the SAT diet.…”
Section: Discussionsupporting
confidence: 85%
“…This development may lead to an increased dietary intake of MUFAs and PUFAs, especially a-linolenic acid (18:3 n-3). Several intervention studies with rapeseed oil-rich diets have shown favourable effects on the blood lipid profile in healthy volunteers (McDonald et al, 1989;Wardlaw et al, 1991;Valsta et al, 1992;Nydahl et al, 1994) and in hyperlipidemic patients (Lichtenstein et al, 1993;Gustafsson et al, 1994;Nydahl et al, 1995). In these studies, serum levels of total and low-density lipoprotein (LDL) cholesterol were reduced, while serum levels of triglycerides and highdensity lipoprotein (HDL) cholesterol remained unchanged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those with average or moderately elevated cholesterol concentrations few studies involving natural foods have been conducted outside of metabolic wards; and when they have, participants have been provided with prepared foods (Mensink & Katan, 1989;Ginsberg et al, 1990;Valsta et al, 1992;Wahrburg et al, 1992;Lichtenstein et al, 1993) or intensive dietary counselling (Ehnholm et al, 1984). A strength of the present study is that it was conducted under normal living conditions, and apart from simple dietary guidelines, subjects were free to select and prepare their own foods.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a number of investigators have studied the differential effects of polyunsaturated and monounsaturated fatty acids on plasma lipoproteins and have reported that the replacement of saturated fat with either class of fatty acids resulted in the lowering of LDL-C concentrations. 13 - 28 Moreover, some investigators have noted that the monounsaturated fatty acidrich diets caused less reduction in HDL-C levels than the polyunsaturated fatty acid-rich diets, while other investigators have not observed such differences. 1328 Differences in study results may relate to the total fat content of the diet as well as the type of subjects studied.…”
mentioning
confidence: 99%